The Oxford handbook of media, technology, and organization studies - Beyes, Timon, 1973-; Holt, Robin, 1966-; Pias, Claus (Oxford : Oxford University Press, 2020)
Our most basic relationship with the world is one of technological mediation. Nowadays our available tools are digital, and increasingly what counts in economic, social, and cultural life is what can be digitally stored, distributed, replayed, augmented, and switched. Yet the digital remains very much materially configured, and though it now permeates nearly all human life it has not eclipsed all older technologies. This handbook is grounded in an understanding that our technologically mediated condition is a condition of organization. It maps and theorizes the largely unchartered territory of media, technology, and organization studies. Written by scholars of organization and theorists of media and technology, the chapters focus on specific, and specifically mediating, objects that shape the practices, processes, and effects of organization.
Account Book / François-Régis Puyou, Paolo Quattrone -- Real time bidding system / Theodore Vurdubakis -- Coffee Machine / Götz Bachmann, Paula Bialski -- Colour Chart / Timon Beyes -- Container / Alexander Klose -- Conversational Interface / Mercedes Bunz -- Desk / Karen Dale, Gibson Burrell -- Elevator / Andreas Bernard -- Executive Dashboard / Armin Beverungen -- Filter System / Wendy Hui Kyong Chun -- Interface / Nishant Shah -- Acoustic Tile / Reinhold Martin -- Mind Tracker / Aleksandra Przegalinska -- Office Plant / Stefan Rieger -- Paper Shredder / Alice Comi -- Planning Table / Lisa Conrad -- Pen / Daniel Hjorth -- Copy Machine / Monika Dommann -- Overhead Projector / Claus Pias -- Prezi / Annika Skoglund -- Battery / Jan Müggenburg -- Price Book / Damian O'Doherty -- Pussyhat / Sine Nørholm Just -- Railyway Tracks / Christian De Cock -- Recommender systems / Jannis Kallinikos, Cristina Alaimo -- Search Engine / Renée Ridgway -- Smartphone / Jennifer Whyte -- High Heels / Mike Zundel -- Suit / Barbara Vinken -- Whiteboard, Flipchart / Jörg Metelmann -- Typeface / Robin Holt -- Wiki / Dariusz Jemielniak, Olga Rodak, Tomasz Raburski -- Telegraph / Mikkel Flyverbom, Anders Koed Madsen -- By means of which: Media, technology and organization studies / Timon Beyes, Robin Holt, Claus Pias -- Bicycle / Christoph Michels, Chris Steyaert -- Calendar / Florian Hoof -- Cloud / John Durham Peters -- Dating App / Nanna Bonde Thylstrup, Kristin Veel -- Push Button / L. Roman Duffner -- Bitcoin / Lucas Introna, Lara Pecis -- Card / Markus Krajewski -- Copper / Ned Rossiter -- Chair / Maria-Laura Toraldo, Jeanne Mengis -- Clock / Melissa Gregg, Tamara Kneese.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 31, 2020).
Keywords: Organizational behavior; Mass media and technology